2015
DOI: 10.20472/es.2015.4.4.001
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Firm Characteristics on IFRS 8 Disclosure in the Transition Period in Nigeria

Abstract: Following the adoption of International Financial Reporting Standard (IFRS) in Nigeria, companies listed under Nigerian Stock Exchange (NSE) are mandated to comply with the provisions of IFRS within the transition period effective 1st January 2012 and ending 2014. The aim of this paper is to share more lights in the transition process to IFRS with regards to segment reporting in mandatory regime. Based on sample of 97 listed companies using a disclosure index, the study document that the quantity of disclosure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 14 publications
(18 reference statements)
2
7
0
Order By: Relevance
“…This outcome is in line with Chukwu et al (2019).The size of a company also has a significant positive effect on compliance with IFRS 1. This notion was also supported by previous studies (Glaum et al, 2013;Ibrahim, 2015;Uyar et al, 2016). On the other…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This outcome is in line with Chukwu et al (2019).The size of a company also has a significant positive effect on compliance with IFRS 1. This notion was also supported by previous studies (Glaum et al, 2013;Ibrahim, 2015;Uyar et al, 2016). On the other…”
Section: Discussionsupporting
confidence: 87%
“…The study also used a checklist for the level of compliance. In Nigeria, Ibrahim (2015) found that all the company attributes listed above are positively associated with compliance with IFRS 8.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In segment information research conducted by Schvirck, Lunkes and Gasparetto (2013) found that large companies will provide more segment information. The same results were also shown by Muhammad and Siregar (2014) and Ibrahim (2015) the size of the company has a positive effect on the extent of segment information disclosure. Alfraih and Alanezi (2011), Alfraih and Alshammari (2016) consistently show that firm size affects the disclosure of operating segments.…”
Section: Effect Of Company Size On the Level Of Disclosure Of Operating Segmentssupporting
confidence: 74%
“…Companies audited by big-4 audit firm tend to provide more disclosures. Alfraih and Alanezi (2011) and Alanezi's research, Alfraih Alshammari (2016) found that companies audited by big-4 audit firm revealed more segment information, as well as research results from Fakfah, Shabou, Pige (2018), Ibrahim (2015) and Muhammad and Siregar (2014) found the same results.…”
Section: Effect Of Quality Of Auditors On Operating Segmentsmentioning
confidence: 79%